Japanglish Pronunciation in Music Video "Tokyo Bon" by Namewee Featuring Meu Ninomiya - Moch Sahril Irfan Ahmad; Ayunita Leliana (Pioneer: Journal of Language and Literature, 2022)
English is used as an international language, but some nations such as Japan used different alphabets to construct the words in their language. Japanese have three types of characters, but they used Katakana to write English words. Due to the inflexibility of Katakana characters, the Japanese pronunciation of English words has become a phenomenon called “Japanglish.” The theory used in this study is BIA+ proposed by Dijkstra and Van Heuven (1998). This study focuses on finding the mispronounced part in Japanglish and the pattern that emerges when Japanglish is used in the lyrics of the song. The data of this study were the lyrics in Japanglish from a video with the title “Tokyo Bon” by Namewee ft. Meu Ninomiya. This study used a qualitative method and documentation as a data collection technique. The results of this study were the findings of the mispronounced positions in Japanglish and the patterns in pronouncing Japanglish such as the substitutions of the consonants and vowels, most words ending with vowels, and shortening the words for more straightforward pronunciation.